Some observations on the propagation of plants from hard-wood cuttings - Thompson, John Bert (My University, 1905)
introduction: Among the many processes of plant propagation, in which the horticulturist is most concerned, that of hard wood cuttings is at least one of the most important. It is not important only because of the great number of species that are reproduced in this was, but also for the ease and consequent cheapness of propagating them. The American Horticulturist is indebted to this process for a majority of his currant and gooseberry bushes, and for a large number of the ornamental shrubs that add so much to the attractiveness of the home and the pleasures of life. While it is not to be expected that the following experiment, which comprises a study of the growth of various plants from hardwood cuttings, will reveal only unknown facts, yet it is hoped that something’s both interesting and instructive may be gained from it. The conditions of the experiment were as follows: Sixteen different species, mostly of ornamental shrubs, were selected from available stock and were chosen for the ease with which they are grown by this method. The young wood was taken between the first and tenth days of January and stored in a moist place in the cellar, where the temperature was fairly constant at about 40? F. in the morning to about 65? F. in the afternoon. As the warm season approached, the average temperature, of course, became much higher. These different cuttings must be considered separately and for the sake of convenience it may be best to arrange them in alphabetical order. Cornus Mascula. – The first signs of growth in these cuttings were observed forty-six days after planting, when the formation of a callus about the cambium of the lower end of the cutting was first noted.
Citation: Thompson, John Bert. Some observations on the propagation of plants from hard-wood cuttings. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Propagation of Hard-Wood Cuttings; Notes on Growgh of Various Species; Nature of the Expeiment; Theses